(untitled) (Bioagro, 2022)
The genus Bacillus produces volatile compounds, plant hormones, polysaccharides and enzymes related to the metabolism of phenylpropanoids, which represents a high potential for plant growth stimulation. This study analyzed the effects of diffusible and organic volatile compounds produced by four endophytic bacterial strains of the genus Bacillus (Bacillus sp. E25, B. toyonesis COPE52, B. thuringiensis UM46 and Bacillus sp. CR71) on the promotion of plant growth of blackberry seedlings, such as the Tupy, Kiowa, and UM-13 genotypes, growing in vitro. The results showed that the diffusible and volatile organic compounds produced by strain COPE52 promoted the length and dry weight of roots, numbers of roots, and chlorophyll concentration in the Tupy cultivar. The emission of diffusible compounds produced by COPE52 also promoted the roots dry weight and aerial parts, and the root length in Kiowa genotype, while volatile compounds produced by strain E25 had stimulating effects on most of analyzed variables in the same genotype. Diffusible and volatile compounds produced by strain CR71 had a major effect on number, length and dry weight of roots of the seedlings of UM-13 genotype, while the concentration of chlorophyll was increased by the same compounds produced by strain E25. Finally, endophytic Bacillus spp. differentially promoted plant growth of four varieties in Rubus sp. seedlings, and their beneficial effect was strain-dependent.